Case Study of Tantrum Behavior in Early Childhood - Tri Nola Mulfiani; Rakimahwati Rakimahwati (STAI Hubbulwathan Duri, 2023)
Emotional development in childhood is a determinant of the attitude and behaviour of children in the future. Not optimally developing children's emotional abilities will cause negative emotions in the form of tantrums. This study aims to describe the tantrum behaviour of children. The purpose of this study was to investigate what causes children to throw tantrums and what parents and educators may do to reduce the occurrence of these outbursts. This research employed a descriptive analysis of a case, or a case study, of two group B children, aged five and six, with tantrum behaviour issues in one of the kindergartens in Bukittinggi City. Two youngsters, RKW and ZP, were studied for their tantrum behaviours. Researchers identified three types of tantrums: manipulative, vocal irritation, and temperamental. When it comes to a child's personal growth, parents and educators play crucial roles. However, parents and instructors can handle toddlers prone to tantrums in one of two ways: either keep a close check on them or ignore them entirely. Once the child has calmed down, they are given simple, straightforward guidance. Hugs are the final piece of advice that parents and teachers may give.